La exclusión del denunciante en el Procedimiento Administrativo Disciplinario de la Policía Nacional del Perú, ¿compatible con un Estado Constitucional de Derecho? - Gonzales Pastor, Nataly (Pontificia Universidad Católica del Perú, 2025)
Law 30714, enacted in 2017, constitutes the regulatory framework governing the conduct and discipline of members of the Peruvian National Police. This legal instrument establishes guiding principles, protected legal interests, the classification of infractions and disciplinary administrative sanctions, as well as the disciplinary procedure applicable to police personnel. This article analyzes the regulatory design of the police Disciplinary Administrative Procedure from a constitutional perspective, focusing on the exclusion of the complainant as a party to the procedure. It argues that this exclusion deviates from the Constitutional State of Law and violates principles such as the right to defense, due administrative process, and effective judicial protection. Furthermore, it prevents the complainant from accessing the case file, participating in the investigation, or challenging decisions such as the dismissal of their complaint, thus fostering institutional discretion and weakening citizen oversight. In this sense, the text examines this problem in light of constitutional jurisprudence, doctrine and international standards, proposing a legal reform that reconfigures the police disciplinary procedure according to a guarantee-based and transparent model, recognizing the complainant as a party with minimal powers of intervention, in protection of the Constitutional State of Law and public interests.

La Ley 30714, promulgada en 2017, constituye el marco normativo que regula la conducta y disciplina de los miembros de la Policía Nacional del Perú. Este cuerpo legal establece principios orientadores, intereses jurídicos protegidos, la clasificación de infracciones y las sanciones administrativas disciplinarias, así como el procedimiento sancionador aplicable al personal policial. El presente artículo analiza el diseño normativo del Procedimiento Administrativo Disciplinario policial desde una perspectiva constitucional, frente a la exclusión del denunciante como sujeto parte del procedimiento. Se sostiene que dicha exclusión se aparta del Estado Constitucional de Derecho y vulnera principios como el derecho de defensa, el debido proceso administrativo y la tutela jurisdiccional efectiva. Además, impide al denunciante acceder al expediente, participar en la investigación o impugnar decisiones como el archivo de su denuncia, lo que favorece la discrecionalidad institucional y debilita el control ciudadano. En ese sentido, el texto examina esta problemática a la luz de la jurisprudencia constitucional, la doctrina y los estándares internacionales, proponiendo una reforma legal que reconfigure el procedimiento disciplinario policial conforme a un modelo garantista y transparente, reconociendo al denunciante como sujeto parte con facultades mínimas de intervención, en protección del Estado Constitucional de Derecho y de los intereses públicos.
Is the exclusion of the complainant in the Disciplinary Administrative Procedure of the National Police of Peru compatible with a Constitutional State of Law?
Keywords: Disciplinary sanction procedure; National Police of Peru; Exclusion of complainant; Constitutional Rule of Law; Procedimiento disciplinario sancionador; Policía Nacional del Perú; Exclusión de denunciante; Estado Constitucional de Derecho; https://purl.org/pe-repo/ocde/ford#5.05.01